Pendampingan Aktif Sejawat untuk Mengatasi Kecemasan Berbicara Bahasa Inggris: Studi Kasus Pembelajar Vokasi - Yerly Datu (JLA (Jurnal Lingua Applicata), 2017)
Speaking anxiety becomes one of the toughest barriers in EFL learning. In the meantime, speaking competence is paramount for vocational graduates at job market. Therefore, big and continuous efforts must be done to maximize the learning outcome. This paper aims to examine how active and guided peer mentoring among learners can actually decrease anxiety of vocationa learners. For the purpose, qualitative research employing a case study design involving fourteen participants of vocational learners taking Speaking II was conducted. Stages including peer mentor screening, peer mentor preparation for guidance, peer mentoring activities, peer mentoring monitoring were applied. Responses from Focus Group Discussions (FGD) among mentors and participants being mentored were collected and analyzed afterwards. Recommendations were also made from best practices generated.